(untitled) (Jurnal Teknologi (Sciences & Engineering), 2017)
The increase of water quality is related to the presence of dissolved oxygen. Even, the oxygen concentration in surface waters is a main indicator of the water quality for human use as well as for the aquatic biota. Air entrainment on stepped spillway is also recognised for its contribution to the oxygen transfer. The oxygen transfer on stepped spillways in skimming flow regime is increased due to earlier self-aeration and slower flow velocities in comparison to smooth spillways. This paper presents the results gained on a physical model by using a variety of different configurations of stepped spillway. The slopes of stepped spillway (Î¸) used are 30Ëš and 45Ëš, the number of step (N) are 40 and 20, and two types of steps are flat steps and pooled steps. The experiments were conducted for ten Froude number (Fr) run ranging from 1.117 to 9.909. This research aimed to investigate the influence of different configuration in stepped spillway for predicting of dissolved oxygen. The results showed that the dissolved oxygen of the stepped spillway increases with an increase in chute of slope, number of step, and surface roughness on steps. The increases of Froude number as a function of discharge will cause turbulence flow becomes decreases, and the concentration of air bubble in the water will be decreased. The decreased value of turbulence flow will make dissolved oxygen level decrease. In skimming flow condition, the dissolved oxygen level decreases with increasing discharge per unit width especially for steep bed slope.Â